2012
DOI: 10.1086/666943
|View full text |Cite
|
Sign up to set email alerts
|

The Appearance and Spread of Ant Fishing among the Kasekela Chimpanzees of Gombe

Abstract: Chimpanzees exhibit cultural variation, yet examples of successful cultural transmission between wild communities are lacking. Here we provide the first account of tool-assisted predation (“ant fishing”) on Camponotus ants by the Kasekela and Mitumba communities of Gombe National Park. We then consider three hypotheses for the appearance and spread of this behavior in Kasekela: (1) changes in prey availability or other environmental factors, (2) innovation, and (3) introduction. Ant fishing was recognized as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 50 publications
(73 reference statements)
0
45
0
1
Order By: Relevance
“…So far only chimpanzees and humans have been found to converge on the behaviour variant that is most common in the group, even if they have alternative behaviours in their individual repertoires that accomplish the same goal just as efficiently [67]. Conformist transmission has been proposed to restrict the accumulation of traditions in non-human [27,37,49] and human [62,68] populations. Therefore, local differences between populations remain despite individual exchange through marriage and migration [69], preventing cross cultural homogenization but protecting cultural diversity among neighbouring communities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far only chimpanzees and humans have been found to converge on the behaviour variant that is most common in the group, even if they have alternative behaviours in their individual repertoires that accomplish the same goal just as efficiently [67]. Conformist transmission has been proposed to restrict the accumulation of traditions in non-human [27,37,49] and human [62,68] populations. Therefore, local differences between populations remain despite individual exchange through marriage and migration [69], preventing cross cultural homogenization but protecting cultural diversity among neighbouring communities.…”
Section: Discussionmentioning
confidence: 99%
“…Only if innovators persist can they add to the behavioural pool by disseminating their innovations once they are older [48,76]. However, the ontogeny of cultural traits within a community remains a topic of investigation as only a few studies have reported the spread of new behaviours within a chimpanzee community [13,49]. In those cases, the spread of the innovations were reported for nonarbitrary behaviours and implied increased fitness through additional foraging sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can have important implications for cultural diversity, 16 with the number of cultural traits in chimpanzee societies correlating with the number of females, 17 not males [89]. Sex-specific social learning will also determine the spread of cultural traits between 18 groups in species with sex-specific dispersal patterns [90]. In humans, socially proscribed roles (e.g.…”
Section: Sex Differencesmentioning
confidence: 99%